ANALYSIS THE INFLUENCE OF INTELLECTUAL CAPITAL ON THE PERFORMANCE OF INDONESIAN COMPANIES - Owen Owen; Hesniati Hesniati (LPPM STIE Muhammadiah Bandung, 2022)
This study was conducted with the aim of determining the relationship between intellectual capital (IC), categorized in five subconstructions- namely, relational capital (RC), process capital (PrC), human capital (HC), technological capital , innovation capital (Innc), and business performance in the manufacturing industry. The sample from this study is a manufacturing company of the consumer goods industry sector registered with IDX. The findings of this study explain that there are three variables, namely HC, RC, and technological capital, which have no effect on company performance while the other two variables, namely InnC and PrC, have a significant positive influence on company performance. Data resource constraints are the main limitations in the process of making this research, because some companies do not fully explain their financial statements, moreover, the study is limited to manufacturers in the consumer goods sector, and it spans only five years.